Reprogramming ThDP Enzymes for Z -Alkenes: Overriding Thermodynamic Preference via Noncovalent Controls - Huangong Li; Tairan Yang; Yilong Zhao; Rui Pan; Jinmin Peng; Yinhong Lai; Jingyu Zhang; Xueting Liu; Guoliang Zhu; Lixin Zhang; Yonggui Robin Chi; Yongtao Xie (Journal of the American Chemical Society, 2026)
Abstract Most conventional alkene synthesis reactions (e.g., elimination et al.) inherently favor the formation of thermodynamically more stable E-isomers, posing a long-standing challenge for direct access to Z-alkenes. Here, we report the reprogramming of a thiamine diphosphate (ThDP)-dependent enzyme to catalyze a formal dehalogenative elimination that overrides this intrinsic thermodynamic bias, enabling the direct and selective synthesis of Z-α,β-unsaturated carboxylic acids. In contrast to classical approaches that rely on substrate control, directing groups, or complex ligand architectures, our strategy harnesses the enzyme’s confined active site to achieve kinetic control exclusively via noncovalent interactions─representing a fundamentally distinct and more sustainable approach to stereochemical programming. This transformation diverts the enzyme from its native function in C–C bond formation by channeling the Breslow intermediate toward a homoenolate-mediated pathway, wherein specific noncovalent interactions stabilize the syn-periplanar geometry required for Z-selective dehalogenative elimination. Through rational active-site engineering, the stereochemical trajectory can be inverted to furnish the complementary E-isomer, enabling stereodivergent synthesis from a common scaffold. This work establishes a biocatalytic platform that addresses a critical gap in Z-alkene synthesis, expands the catalytic repertoire of ThDP-dependent enzymes, and provides a sustainable alternative to conventional methodologies.